INOVASI PEMERINTAH DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PADA MASA COVID-19 DI KOTA PEKANBARU - Sekar Harum Ning Utami; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The many deviant phenomena in the process of population administration services carried out by irresponsible parties need to be addressed immediately so that they do not become increasingly attached to the officials on duty. Besides that, the existence of the Covid-19 outbreak that has hit all of Indonesia has had an impact on various fields. Especially in public service sector, namely the Population Administration Services by the Department of Population and Civil Registration at Pekanbaru City which was hampered. The need to innovate to improve the quality of service and maintain the course of service, especially in the Covid-19 situation. This study aims to discover the innovations made by the City Government, in this case, it's the Department of Population and Civil Registration at Pekanbaru City in improving administrative services for the people of Pekanbaru City during the Covid-19 pandemic in 2021 to 2022 during the transition period. This research method uses a qualitative approach with a descriptive research type. Data collection techniques used in this study were interviews and documentation. The results of the study show that the Government of Pekanbaru City, especially the Department of Population and Civil Registry of Pekanbaru City, has carried out a service innovation called Sipenduduk which is a website-based application for making population documents so that applications for managing population documents are now online. In particular, for the collection of e-KTP population documents still taken directly to the Department of Population and Civil Registry of Pekanbaru City. However, the Department of Population and Civil Registry of Pekanbaru City is still experiencing some obstacles related to network, full servers, and problematic user data. On the other hand, people also experience problems in using Sipenduduk. There are still many people who do not understand how to use Sipenduduk. Besides, the many lines that must be passed make people who want to take population document products at the office confused, because there is no information regarding the route that must be passed at the Department of Population and Civil Registry of Pekanbaru City office. Keywords: Innovation Principle, Population Administration Service, Innovation Attribute